Dinâmica de rotação de exoplanetas tipo terrestre com perturbação de terceiro corpo - Ribeiro, Filipe Batista [UNESP] (2012)
In this work we study some topics of Celestial Mechanics, namely the problem of rigid body rotation and “spin-orbit” resonances. Emphasis is placed on the problem formulation and applications to some exoplanets with physical parameters (e.g. mass and radius) compatible with a terrestrial type constitution (e.g. rock) belonging to multiple planetary systems. The approach is both analytical and numerical. The analytical part consists of: i) the deduction of the equation of motion for the rotation problem of a spherical body with no symmetry, disturbed by a central body; ii) modeling the same problem by including a third-body in the planet-star system; iii) formulation of the concept of “spin-orbit” resonance in which the orbital period of the planet is an integer multiple of the rotation’s period. Topics of dynamical systems (e.g. equilibrium points, chaos, surface sections, etc.) will be included at this stage. In the numerical part simulations are performed with numerical models developed in the previous analytical section. As a first step we consider the orbit of the planet not perturbed by a third-body in the star-planet system. In this case the eccentricity and orbital semi-major axis of the planet are constants. Here the technique of surface sections, widely used in dynamical systems are applied. Next, we consider the action of a third body, developing a more realistic model for planetary rotation. The results in both cases are compared. Since the technique of disturbed surface sections is no longer applicable, we quantitatively evaluate the evolution of the characteristic angles of rotation (e.g. physical libration) by studying the evolution of individual orbits in the dynamically important regions of phase space, the latter obtained in the undisturbed case